The acute effects of green tea and carbohydrate coingestion on systemic inflammation and oxidative stress during sprint cycling - Suzuki, K.; Takahashi, M.; Li, C.-Y.; Lin, S.-P.; Tomari, M.; Shing, C. M.; Fang, S.-H. (Applied Physiology, Nutrition, and Metabolism, 2015)
Green tea (Camellia sinensis) has anti-oxidative and anti-inflammatory effects, which may be beneficial to athletes performing high-intensity exercise. This study investigated the effects of carbohydrate and green tea coingestion on sprint cycling performance and associated oxidative stress and immunoendocrine responses to exercise. In a crossover design, 9 well-trained male cyclists completed 3 sets of 8 repetitions of 100-m uphill sprint cycling while ingesting green tea and carbohydrate (TEA) (22 mg/kg body mass catechins, 6 mg/kg body mass caffeine, 230 mg/kg glucose, and 110 mg/kg fructose) or carbohydrate only (CHO) (230 mg/kg body mass glucose and 110 mg/kg body mass fructose) during each 10-min recovery period between sets. Blood samples were collected before exercise, 10 min after exercise, and 14 h after exercise. There was no effect of acute TEA ingestion on cycling sprint performance (p = 0.29), although TEA maintained postexercise testosterone and lymphocyte concentrations, which decreased significantly in the CHO group (p < 0.001). While there was a trend for lower postexercise neutrophil count with TEA (p = 0.05), there were no significant differences between TEA and CHO for circulating cytokines (p > 0.20), markers of oxidative stress and antioxidant capacity (p > 0.17), adiponectin concentration (p = 0.60), or muscle damage markers (p > 0.64). While acute green tea ingestion prevents the postexercise decrease in testosterone and lymphocytes, it does not appear to benefit cycling sprint performance or reduce markers of oxidation and inflammation when compared with carbohydrate alone.